(3x+3)-(4x+8)=
=3x+3-4x-8=
= (3x-4x)+(3-8)=
=-x+(-5)=
=-x-5
Answer:
The correct answer is 6x +7
Step-by-step explanation:
It is given a polynomial 6x^2 + x − 7
Factorization of 6x^2 + x − 7
Using splitting method
6x^2 + x − 7 = 6x^2 - 6x + 7x − 7
= 6x(x - 1) + 7 (x - 1) (take 6x and 7 as common)
= (x - 1)(6x +7)
Therefore the factors of 6x^2 + x − 7 are (x - 1) and (6x + 7)
Therefore the correct answer is (6x + 7)
Answer:
6x+7
Step-by-step explanation:
If you factor this quadratic,
your 2 factors are:
(6x+7)(x-1)
So, it would be the wisest to work in decimals for this problem.
So we have to divide 12.125 by 1.8125 to see how many times the latter goes into the former.
So, since the problem asks for how many lengths can go in without remainder, our answer would simply be 6.